The administration of exogenous prostaglandin may improve ovulation in pacu (Piaractus mesopotamicus) - Criscuolo-Urbinati, E. [UNESP]; Kuradomi, R. Y. [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP]; Batlouni, S. R. [UNESP] (Elsevier B.V., 2012)
Based on the reports of unsuccessful ovulation in pacu (Piaractus mesopotamicus) by fish farmers and researchers undertaking artificial reproduction programs, we evaluated the use of prostaglandin F (PGF) to improve pacu ovulation. This study was conducted during two spawning seasons (2009/2010 and 2010/2011) with two samplings in the first season and one sampling in the second season. A total of 45 females was sampled in this study. The control group was injected with carp pituitary extract (crude extract, 6 mg/kg), and the treatment group received PGF (2 mL per fish in the 2009/2010 season and 5 mL per fish in the 2010/2011 season) in addition to the crude extract. In both seasons, 100% (N = 4, 2009/2010 first sampling; N = 5, 2009/2010 second sampling; and N = 3, 2010/2011) of the PGF-treated fish spawned. In contrast, 53.0% (N = 9) and 83.3% (N = 10) of the control fish spawned in the first and second samplings of the 2009/2010 season, respectively, and only 25.0% (N = 1) spawned in the 2010/2011 season. Fecundity, fertility, and hatching rates did not differ (P > 0.05) between the treated and control fish. Based on oocyte volume frequency analysis, ovaries of the control fish had more (P < 0.05) vitellogenic oocytes with germinal vesicle breakdown that remained unovulated after spawning, whereas more (P < 0.05) of previtellogenic oocytes were present in the ovaries of the PGF-treated fish. In conclusion, administration of exogenous prostaglandin may improve the outcome of hormonally induced spawning in tropical migratory fish. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Pacu; Prostaglandins; Ovulation; Ovarian follicles